(untitled) (Práxis Educativa, 2021)
This paper aims to discuss the use of Digital Information and Communication Technologies (DICT) related to contemporary educational demands. To do so, the study of Brazilian education was chosen using the analytical key proposed by Paulo Freire in his advocacy of the ongoing formation processes. Apart from the cultivated provisions by the referred technologies and its impact in many social bodies, the article tries to investigate the context of the power structures that these technologies stand with the purpose to make it fit to the improvement of the teaching and learning processes to emancipate the school staff. Keywords: Ongoing formation. Digital information and communication technologies. School education.